2009
DOI: 10.1093/hmg/ddp010
|View full text |Cite
|
Sign up to set email alerts
|

Down syndrome--recent progress and future prospects

Abstract: Down syndrome (DS) is caused by trisomy of chromosome 21 (Hsa21) and is associated with a number of deleterious phenotypes, including learning disability, heart defects, early-onset Alzheimer's disease and childhood leukaemia. Individuals with DS are affected by these phenotypes to a variable extent; understanding the cause of this variation is a key challenge. Here, we review recent research progress in DS, both in patients and relevant animal models. In particular, we highlight exciting advances in therapy t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
167
0
26

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(195 citation statements)
references
References 132 publications
2
167
0
26
Order By: Relevance
“…Trisomy 21 results in DS, which is generally considered to be due to dosage imbalance caused by the extra copy of chromosome 21 and occurs at a frequency of more than 1/1,000 in human populations (36). Most trisomies are incompatible with life and are not observed in live births.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Trisomy 21 results in DS, which is generally considered to be due to dosage imbalance caused by the extra copy of chromosome 21 and occurs at a frequency of more than 1/1,000 in human populations (36). Most trisomies are incompatible with life and are not observed in live births.…”
Section: Resultsmentioning
confidence: 99%
“…Several genes on chromosome 21 have been identified as DSrelated genes (36,37). For example, a 1.5-fold increase in dosage of DSCR1 and DYRK1A has been shown experimentally to lead to features of the DS phenotype (38).…”
Section: Resultsmentioning
confidence: 99%
“…1,3 Several studies demonstrated that it inhibits selectively monoamine oxidases, 4 which play a key role in psychiatric and neurological disorders 5 (depression and Parkinson's diseases). Harmine was also identified as a potential inhibitor of the kinase Dyrk1A that is implicated in the pathogenesis of Down syndrome, 6 a common hereditary disorder.…”
Section: Introductionmentioning
confidence: 99%
“…4 Although all individuals with DS manifest these phenotypes, there is significant phenotypic variability between such individuals. 5 In conjunction with these phenotypic traits, DS individuals suffer from a higher incidence of several conditions, including CHDs. 5 The (birth) prevalence of CHDs in DS is about 40-60%, most frequently atrioventricular septal defects and ventricular septal defects.…”
Section: Introductionmentioning
confidence: 99%
“…5 In conjunction with these phenotypic traits, DS individuals suffer from a higher incidence of several conditions, including CHDs. 5 The (birth) prevalence of CHDs in DS is about 40-60%, most frequently atrioventricular septal defects and ventricular septal defects. [6][7][8] Efforts have been made to determine the critical chromosomal region for specific phenotypic features of DS by deletion mapping and characterization of patients with partial trisomy 21.…”
Section: Introductionmentioning
confidence: 99%